Theoretical prerequisites of creation of cement composites of the increased impermeability - B. S. Lesovik; R. S. Fedyuk (Вестник СибАДИ)
The paper deals with the development of composite binders to produce concrete with improved characteristics of gas, water and water vapor permeability. The processes of formation of composite materials in order of decreasing scale levels from the macro to the nanostructure. The criteria for the optimization of the number of the dispersed additives in concrete. In theory, we studied the technological features of the formation of hydrated cement stone structure. Nanodispersed predict a positive effect of additives on the structure and physico-mechanical properties of cement composite materials.